Are there any differences between family and non-family firms in the open innovation era? Lessons from the practice of European manufacturing companies. (2017) - Lazzarotti, Valentina; Visconti, Federico; Pellegrini, Luisa; Gjergji, Rafaela
This study explores the open innovation (OI) choices in terms of partner-type, their determinants and the related innovation performance in family firms (FFs) with respect to non-FFs by means of a European cross-country survey. Results show that FFs are in general less open than non-FFs when we consider openness in terms of breadth, while they are more open when we consider openness in terms of depth. Distinctive determinants of depth for FFs regards the level of aggressiveness of their innovation strategy when scientific partners are considered. These partners are more important for FFs than for non-FFs to achieve efficiency-type performance. Moreover, a peculiar context shapes the relationship between partner-type depths and innovation performance: the external social capital (ESC) is more relevant for FFs to achieve novelty-type performance, while the internal social capital (ISC) exerts a particularly negative role for them when efficiency-type performance is considered.